AtMYB12-Expressing Transgenic Tobacco Increases Resistance to Several Phytopathogens and Aphids - Ding, Xiangyu; Zhang, Haimiao; Li, Ming; Yin, Ziyi; Chu, Zhaohui; Zhao, Xiangyu; Li, Yang; Ding, Xinhua (Frontiers in Agronomy, 2021)
Phytopathogens and pets are two major factors which limit the growth of plants. The expression of a flavonoid regulator gene, AtMYB12, has been reported to increase the endogenous flavonoid contents of tobacco and tomato. Here, we reported that transgenic tobacco carrying AtMYB12 was more resistant to R. solanacearum by activating the up-regulated expression of several defense-related markers, including NbPR1a, NbNOA1 and NbrbohB, suggesting that priming a plant’s defense may contribute to bacterial disease resistance. The improvement of the resistance of AtMYB12-expressing transgenic tobacco is achieved by promoting the production of ROS, H2O2 and NO. AtMYB12-expressing transgenic tobacco also has resistance to fungal pathogens, including Colletotrichum nicotianae Averna and Alternaria alternate. Enrichment of flavonols components, such as rutin, which directly inhibited the growth of C. nicotianae and A. alternate, may also contribute to the defense mediated by AtMYB12 over-expression. At the same time, the results also confirmed that AtMYB12-expressing transgenic tobacco enhanced plant resistance to aphids-infested (Aphidoidea) pets. These results suggested that AtMYB12 gene is a good candidate for pest and disease control, enduing with limited resistance costs and enrichment in flavonols.